2012
DOI: 10.1038/ejhg.2012.24
|View full text |Cite
|
Sign up to set email alerts
|

One thing leads to another: the cascade of obligations when researchers report genetic research results to study participants

Abstract: Even as debate continues about the putative obligation to proactively report genetic research results to study participants, there is an increasing need to attend to the obligations that might cascade from any initial report. We conducted an international, quasi-experimental survey of researchers involved in autism spectrum disorders (ASD) and cystic fibrosis (CF) genetics to explore perceived obligations to ensure updated information or relevant clinical care subsequent to any initial communication of researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…In addition, 'cascading care obligations' such as the provision of treatment may be burdensome or impossible for researchers to provide (Bookman et al 2006). Despite this, a recent survey of researchers found that most (n=290/343, 85 %) felt an obligation to ensure that participants have access to clinical services related to research findings (Miller et al 2012).…”
Section: The Differences Between the Research And Clinical Contextsmentioning
confidence: 99%
“…In addition, 'cascading care obligations' such as the provision of treatment may be burdensome or impossible for researchers to provide (Bookman et al 2006). Despite this, a recent survey of researchers found that most (n=290/343, 85 %) felt an obligation to ensure that participants have access to clinical services related to research findings (Miller et al 2012).…”
Section: The Differences Between the Research And Clinical Contextsmentioning
confidence: 99%
“…Data from responses to other questions are reported elsewhere. 44,45 Both the attitude questions in the non-experimental component of the questionnaire and the professional judgments elicited in response to each vignette were measured using 5-point Likert scales from strongly agree to strongly disagree.…”
Section: Survey Instrumentmentioning
confidence: 99%
“…The lady in the court case and other people with the potential of carrying the gene for Huntington's disease have had first-hand experience with genetic discrimination (Bombard et al, 2012;Erwin et al, 2010 Jaitovich Groisman et al, 2014;Kerath et al, 2013;Ormond and Cho, 2014;Rothstein and Epps, 2001). Participation in a trial where PGx information is collected may lead to finding out that the individual is likely to develop a particular disease or not respond to therapy which in turn may not only have a negative emotional effect on the person's well-being, but may also may oblige the clinician to treat participants differently and provide care not provided to nonparticipants (Hayeems et al, 2013;Miller et al, 2012). The issue of informed consent as it relates to requesting children's genetic tests is also a concern.…”
Section: Genetic Discriminationmentioning
confidence: 99%